When gay people get married : what happens when societies legalize same-sex marriage - Badgett, M. V. Lee (Mary Virginia Lee) (New York : New York University Press, 2016)
Using research conducted in the Netherlands, where same-sex marriage has been permitted since 2001, this work explores the social phenomena of marriage between gay couples.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Same-sex marriage -- Law and legislation; Gay couples -- Legal status, laws, etc; Law; LGBTQ+ Interest; United States of America, USA; Gay & Lesbian studies; Sociology: family & relationships; Laws of specific jurisdictions & specific areas of law; Family law: marriage, separation & divorce